‘Cette exécution mémorable’ : les représentations visuelles de l’exécution de Charles Ier de Milton à la Glorieuse Révolution - Anne-Laure de Meyer (Etudes Epistémè, 2009)
Milton’s attack on Charles I must be situated within the wider study of the iconographical representations of kings and tyrants, as well as of the deaths of kings. This paper shows that many aspects of the political discourse also find their counterparts in a form of visual discourse.